Tindak Kekerasan Terhadap Anak di Lingkungan Satuan Pendidikan dan Peranan Keluarga Sebagai Upaya Non-Penal Dalam Pencegahan - Jetty Martje Patty; Cindy Agnesia Ratmala (Criminal of Law Department, Faculty of Law, Pattimura University, 2020)
ABSTRACT ROLE OF THE FAMILY AS A NON PENAL EFFORT IN PREVENTING ACTS OF VIOLENCE AGAINTS CHILDREN IN THE EDUCATION UNIT ENVIRONMENT Schools are required to be anti violence zones, which provides a safe comfortable and enjoyable learning environment. Legal protection made by the government has not provided protection for children from violence that occurs in schools. So that there needs to be other efforts beyond legal measures that can prevent acts of violence against children in school. Non penal efforts through the role of the family.a as the first educational institution in society that plays a role in educating children to shape the character of children. Character education in the family will produce anti violence behavior in children themselves will distance themselves from behavior u violence, because children are equipped with loving behavior, tenderness, religious values, empathy in children.